The Impacts of Dietary Fermented Mao-tai Lees on Growth Performance, Plasma Metabolites, and Intestinal Microbiota and Metabolites of Weaned Piglets - Li, Zhihua; Zhu, Qian; Azad, Md. Abul Kalam; Li, Huawei; Huang, Pan; Kong, Xiangfeng (Frontiers in Microbiology, 2021)
This study investigated the effects of dietary supplementation with fermented Mao-tai lees (FML) on growth performance, plasma metabolites, and intestinal microbiota and metabolites of weaned piglets. A total of 128 Duroc × Landrace × Yorkshire piglets (28 day-old) were randomly assigned to one of four groups, feeding a basal diet (control group), a basal diet supplemented with 2%, 4%, or 6% FML, respectively, for 42 days. The results showed that dietary 4% FML supplementation had higher (P < 0.05) average daily gain (ADG) and plasma triglyceride concentration during days 1−14 of the trial than the other FML supplemented groups. In addition, dietary 2% and 4% FML supplementation increased (P < 0.05) the ADG during days 15−28 of the trial and plasma total protein concentration on day 42 of the trial compared with the 6% FML supplement. The plasma concentrations of arginine, ethanolamine, histidine, isoleucine, lysine, methionine, proline, taurine, threonine, and tyrosine were increased (P < 0.05) in the 4% FML group compared with the other three groups on day 14 of the trial. Dietary supplementation with 2−6% FML decreased (P < 0.05) the plasma urea nitrogen concentration on day 14 of the trial and the abundance of Escherichia coli in the colon, and dietary 2% and 4% FML supplementation decreased (P < 0.05) the abundance of sulfate-reducing bacteria compared with the control group. In the intestinal contents, a higher concentration of FML (6%) supplementation decreased (P < 0.05) the colonic acetate concentration compared with the control and 2% FML groups, while 4% FML supplementation increased (P < 0.05) the colonic cadaverine concentration compared with the other three groups. In conclusion, dietary 4% FML supplementation might contribute to the increased amino acids metabolism without affecting the growth performance of weaned piglets. Moreover, dietary 2% and 4% FML supplementation were also beneficial to intestinal health via decreasing the abundances of specific pathogens and increasing the concentrations of microbial metabolites in the gut, which provides the theoretical basis and data support for the application of FML in pigs.